Treponema pallidum tprII subfamily genes internal fragments sequencing - Xenia I. Plakhova; Alexander V. Chestkov; Nazerbek K. Abuduev; Michael M. Vasiliev (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Background. The modern system of molecular typing of the Russian population of T. pallidum makes it possible to obtain results with a significant dominance of the 14d/f type, which determines the need to increase the differentiating ability of the applied methods of molecular typing of T. pallidum. Aim. Identification and analysis of nucleotide sequence variability of internal gene fragments of the tprII family of Russian T. pallidum subsp. pallidum strains. Material and methods. The study of internal variable fragments of genes of the tprII family was carried out among 240 clinical isolates of T. pallidum obtained from the Central (Kaluga Region, Moscow), North Caucasian (Stavropol Territory), Far East (Republic of Sakha), Volga (Chuvash Republic), Southern (Astrakhan Region) and Siberian (Novosibirsk and Omsk Regions, Republic of Tyva) federal districts in 20142020. The sequence of internal variable fragments of genes of the tprII family was determined using capillary sequencialng technology. Results. The primers allowing both direct amplification of the internal variable region of the tprII genes subfamily and correct sequencing of their internal regions have been proposed. It was found one SNP at positions 1340 of tprG gene. The polymorphism differs the reference Nichols strain from globally distributed Street 14 genogroup variants. Conclusion. The variability of tprII subfamily genes nucleotide sequences in modern Russian strains of T. pallidum subsp. pallidum is an additional fund to increase the efficiency of the modern T. pallidum molecular typing system.